The importance of the rotor in hydrazone-based molecular switches - Xin Su; Timo Lessing; Ivan Aprahamian (Beilstein Journal of Organic Chemistry, 2012)
The pH-activated E/Z isomerization of a series of hydrazone-based systems having different functional groups as part of the rotor (R = COMe, CN, Me, H), was studied. The switching efficiency of these systems was compared to that of a hydrazone-based molecular switch (R = COOEt) whose E/Z isomerization is fully reversible. It was found that the nature of the R group is critical for efficient switching to occur; the R group should be a moderate H-bond acceptor in order to (i) provide enough driving force for the rotor to move upon protonation, and (ii) stabilize the obtained Z configuration, to achieve full conversion.